Exploring the Ambidexterity Landscape: A Comprehensive Bibliometric Analysis of Organizational Change Research - Rosari, Reni; Ardianto, Heni; Danarilia, Vania Olivine (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
The development of literature regarding ambidexterity needs to include the discussion in the strategic renewal amidst increasingly dynamic organizational changes. This research aims to conduct a bibliometric analysis of the ambidexterity literature in the context of organizational change. The reviewed articles were taken from the Scopus database, consisting of 314 articles from 2003 to November 2022 using PoP software. Bibliometric analysis is carried out with the help of VOS Viewer to build, visualize, and explore bibliometric networks. This study uses systematic data to uncover emerging trends and qualitative inductive analysis to determine relevant themes within the topic. The results show that ambidexterity can improve the performance and viability of complex businesses. Overall, this review highlights the importance of ambidexterity in organizational success and suggests avenues for further research to deepen academic understanding and increase practical applications.